Pengaruh Sistem Catur Wangsa terhadap Perwujudan Tata Spasial Kota Peninggalan Kerajaan Hindu di Bali: Kasus Kota Karangasem - I Gusti Ngurah Wiras Hardy; Bakti Setiawan; Budi Prayitno (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
Karangasem City is one of the heritage cities of Karangasem Kingdom in Bali which has a typical spatial layout and society life. The society of Karangasem City is divided into several classes based on the catur wangsa (social group) which is presumed affecting the realization of spatial layout of Karangasem City physically. It is interesting to conduct a deeper investigation on it to identify the effect of the system, so that it can be used as an input to manage and develop Karangasem City in the future. In investigating the effect, the method used in this study is qualitative method with inductive-qualitative technique and three data collection techniques, they are field observation, in-depth interview with purposive sampling, and literature study. Based on the results of the study, it is understood that the catur wangsa system took part in affecting the spatial layout of Karangasem City in which divided the city area into three layers of concentric circles according to the level of social classes that inhibits each of the layers. It also shows the suitability of Karangasem City spatial layout with the tri mandala (three spaces) concept which divides the area of Karangasem City into three layers.